A Legal Analysis Of Inheritance Property Objects Still Serving As Debt Collateral - Azzumar Azza Akbar; Hasim Purba; Rosnidar Sembiring (SEAN Institute, 2024)
The problem of inheritance distribution is one of the issues that often causes disputes in society, especially when it is related to assets that still have burdens or ties to other parties. One form of complexity in inheritance distribution occurs when the object of inheritance still has the status of debt collateral. This research is a normative legal research supported by interview data, descriptive nature of analysis using a legislative approach and a conceptual approach. The methodology of this research relies on secondary data. Data collection is done through library research, while data analysis uses qualitative methods. This decision has a significant impact as a new jurisprudence that changes the previous paradigm from rejection of the lawsuit (NO) to the concept of inheritance distribution that can still be implemented by paying attention to the protection of the rights of heirs and creditors, thus creating a new standard in religious court practice for handling similar cases in the future.